Clinical Examination Findings Can Accurately Diagnose Developmental Dysplasia of The Hip-A Large, Single-Center Cohort - İzzet Özay Subaşı; Enejd Veizi; Şahin Çepni; Hilmi Alkan; Temel Oğuz; Ahmet Fırat (MDPI AG, 2023)
Background: Physical examination findings such as limited hip abduction (LHA), asymmetric skin creases (ASC), and a popping sensation in the hip facilitate the diagnosis of developmental dysplasia of the hip (DDH). Screening with a simple physical examination during the first weeks of infancy is important for early detection of the condition, and a wide range of medical professionals, including general practitioners, obstetricians, pediatricians, and orthopedic surgeons etc. are involved in this process. The aim of this study was to determine the correlation between easily recognizable physical examination findings such as LHA, thigh/groin ACSs, and Ortolani and Barlow tests with ultrasound findings for the diagnosis of DDH. Methods: This study included 968 patients undergoing routine hip ultrasonography between December 2012 and January 2015. All patients were examined by an experienced orthopedic surgeon who was not the physician who performed the ultrasound examination to exclude bias between physical examination findings and ultrasound findings. Asymmetric skin folds (thigh and groin), limited abduction, Barlow and Ortolani tests were recorded. The relationship between the physical examination findings, ultrasound findings, and developmental dysplasia was investigated. Results: Of the 968 patients, 523 were female (54%) and 445 were male. On ultrasonography examination, 117 patients were found to have DDH. The sensitivity, specificity and negative predictive values of patients who were found to have both LHA and thigh/groin ASCs in all three physical examinations were high (83.8%, 70.2%, and 96.9%, respectively) while positive predictive values were found to be low (27.8%). Conclusion: Asymmetric skin creases on the thigh and groin and limited hip abduction, when evaluated together, have high sensitivity and specificity with additional high negative predictive values and could help during the initial screening process of DDH.